Last-minute science fair projects : when your Bunsen's not burning but the clock's really ticking - Bardhan-Quallen, Sudipta (New York : Sterling Pub., 2006)
Examines ways to complete your science project in a very short time with supplies you can find around the house.
Includes index.
Keywords: Science projects -- Juvenile literature; Science projects